Draft Annual Plan 1988-89 Volume-V General Areas Government of Assam - Planning Commission (Planning Commission, 1988)
It may be added here that at present there is no system of collection of net enrolment figure. Therefore, the existing Gross enrolment figure includes both under aged and over aged children. Besides the dropout problems are also there. Therefore, we shall have to cover about 4.00 lakhs addl. children in the primary stage in order to achieve 100% enrolment target as proposed in the Draft 7th Five year plan.
Government of Assam, Planning and Development Department